Annals of Clinical Microbiology and Antimicrobials - Leblebicioglu, Hakan; Rodriguez-Morales, Alfonso
Annals of Clinical Microbiology and Antimicrobials considers manuscripts on all aspects of clinical microbiology, infectious diseases and antimicrobials. Submitted manuscripts can report on: any aspect of diagnosis of infectious diseases; biological aspects of infectious diseases; case management and antimicrobial treatment; antibiotic development and antimicrobial resistance. Annals of Clinical Microbiology and Antimicrobials is an open access, peer-reviewed journal focusing on information concerning clinical microbiology, infectious diseases and antimicrobials. The management of infectious disease is dependent on correct diagnosis and appropriate antimicrobial treatment, and with this in mind, the journal aims to improve the communication between laboratory and clinical science in the field of clinical microbiology and antimicrobial treatment. Annals of Clinical Microbiology and Antimicrobials is an international journal with a broad scope, incorporating microbiology and antimicrobials in almost all branches of human medicine. Furthermore, the journal has no restrictions on space or access; this ensures that the journal can reach the widest possible audience.